1998
DOI: 10.3347/kjp.1998.36.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Subgenus classification of Acanthamoeba by riboprinting

Abstract: Subgenus classification of Acanthamoeba remains uncertain. Twenty-three reference strains of Acanthamoeba including 18 (neo)type-strains were subjected for classification at the subgenus level by riboprinting. PCR/RFLP analysis of 18S rRNA gene (rDNA). On the dendrogram reconstructed on the basis of riboprint analyses, two type-strains (A. astronyxis and A. tubiashi) of morphological group 1 diverged early from the other strains and were quite distinct from each other. Four type-strains of morphological group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 30 publications
2
48
0
Order By: Relevance
“…Chung et al 26 identified by riboprinting the 'Chang' strain of A. castellanii (T4 equivalent) from fresh water and found it closely related to A. hatchetti (T11 equivalent) isolated from ocean sediments (salt water); both strains were expected to be pathogenic in animal models. The relationship between Acanthamoeba genotype T4 causing keratitis in humans and T4 isolates from organs of fishes, where its role in surviving without causing disease is that of a protozoon parasite, is intriguing.…”
Section: Molecular Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Chung et al 26 identified by riboprinting the 'Chang' strain of A. castellanii (T4 equivalent) from fresh water and found it closely related to A. hatchetti (T11 equivalent) isolated from ocean sediments (salt water); both strains were expected to be pathogenic in animal models. The relationship between Acanthamoeba genotype T4 causing keratitis in humans and T4 isolates from organs of fishes, where its role in surviving without causing disease is that of a protozoon parasite, is intriguing.…”
Section: Molecular Epidemiologymentioning
confidence: 99%
“…Riboprinting involves PCR followed by RFLP analysis of complete 18S rRNA genes. 12 Although comparisons using all the same strains are unavailable, phylogenetic trees based on RFLP riboprints 12,26 appear to identify clusters of related strains similar to those identified based on DNA sequencing. 18 The use of mitochondrial 16S rDNA for riboprinting has the advantage that it avoids distortions of interstrain relationships caused by introns that occasionally occur in the nuclear 18S rRNA genes of some strains.…”
Section: Molecular Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Riboprinting, PCR-RFLP analysis of 18S rDNA, is a simpler and less expensive substitute for 18S rDNA sequence analysis (Clark and Diamond, 1997). Chung et al, (1998) applied riboprinting to subgenus classification of Acantamoeba. The results were congruent with those of sequence analysis.…”
Section: Introduction 1995)mentioning
confidence: 99%
“…P3 (5' CCGAATTCGTCGACAACTGTTGATCCT GCCAGGT 3') and P4 (5' GGATCCAAGCTTGATCCTT CTGCAGGTTCACCTAC 3') (Bhattacharya et al, 1998;Chung et al, 1998). All amplification reactions of PCR were performed in a 50 µl mixture containing 50 ng DNA, 0.2 mM each of dATP, dCTP, dGTP, dTTP, 50 mM of MgCl 2 , 2 µl SAB (serum albumin bovin), 20 pmol of each primer and 2.5 UI of GoTaq DNA polymerase (Promega, Madisson, USA).…”
Section: Note De Recherchementioning
confidence: 99%